2011
DOI: 10.1016/j.fuel.2010.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Physical–chemical properties of waste cooking oil biodiesel and castor oil biodiesel blends

Abstract: This work presents the physical-chemical properties of fuel blends of waste cooking oil biodiesel or castor oil biodiesel with diesel oil. The properties evaluated were fuel density, kinematic viscosity, cetane index, distillation temperatures, and sulfur content, measured according to standard test methods. The results were analyzed based on present specifications for biodiesel fuel in Brazil, Europe, and USA. Fuel density and viscosity were increased with increasing biodiesel concentration, while fuel sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 6 publications
2
32
0
5
Order By: Relevance
“…Meanwhile, the chemical composition of palm oil methyl ester using GC-MS mostly consisted of 40.2% palmitic acid methyl ester and 42.4% oleic acid methyl ester. The production of biodiesel from other feedstocks, such as castor oil, soybean oil, and waste cooking oil, has been conducted by many previous researchers (Valente et al, 2011;Ganjehkaviri, 2018;Aworanti et al, 2012;Doll et al, 2008;Doll et al, 2010). Table 1 shows that biodiesel from soybean oil and palm oil provides good results.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the chemical composition of palm oil methyl ester using GC-MS mostly consisted of 40.2% palmitic acid methyl ester and 42.4% oleic acid methyl ester. The production of biodiesel from other feedstocks, such as castor oil, soybean oil, and waste cooking oil, has been conducted by many previous researchers (Valente et al, 2011;Ganjehkaviri, 2018;Aworanti et al, 2012;Doll et al, 2008;Doll et al, 2010). Table 1 shows that biodiesel from soybean oil and palm oil provides good results.…”
Section: Resultsmentioning
confidence: 99%
“…The high PP and CP will restrict the usage of CNOEE in cold and arctic regions. Blending biodiesel with either fossil diesel or kerosene has been identified to provide a significant improvement [55,56] to the PP and CP of biodiesel.…”
Section: Optimum Parametersmentioning
confidence: 99%
“…The use of waste cooking oil as feedstock can effectively reduce the cost of biodiesel by 60-70%. Biodiesel is used as a mixture constituent of petroleum diesel in proportions for running a diesel engine, since using neat biodiesel has some engine issues (Valente et al 2011). It has been reported that mixing of 5% of biodiesel fuel to the present fuel can save Rs.…”
Section: Introductionmentioning
confidence: 99%